Subject-Independent Cuff-Less Blood Pressure Monitoring via Multivariate Analysis of Finger/Toe Photoplethysmography and Electrocardiogram Data - Seyedmohsen Dehghanojamahalleh; Peshala Thibbotuwawa Gamage; Mohammad Ahmed; Cassondra Petersen; Brianna Matthew; Kesha Hyacinth; Yasith Weerasinghe; Ersoy Subasi; Munevver Mine Subasi; Mehmet Kaya (BioMedInformatics, 2025)
(1) Background: Blood pressure (BP) variability is an important risk factor for cardiovascular diseases. Still, existing BP monitoring methods often require periodic cuff-based measurements, raising concerns about their accuracy and convenience. This study aims to develop a subject-independent, cuff-less BP estimation method using finger and toe photoplethysmography (PPG) signals combined with an electrocardiogram (ECG) without the need for an initial cuff-based measurement. (2) Methods: A customized measurement system was used to record 80 readings from human subjects. Fifteen features with the highest dependency on the reference BP, including time and morphological characteristics of PPG and subject information, were analyzed. A multivariate regression model was employed to estimate BP. (3) Results: The results showed that incorporating toe PPG signals improved the accuracy of BP estimation, reducing the mean absolute error (MAE). Using both finger and toe PPG signals resulted in an MAE of 9.63 ± 12.54 mmHg for systolic BP and 6.76 ± 8.38 mmHg for diastolic BP, providing the lowest MAE compared to previous methods. (4) Conclusions: This study is the first to integrate toe PPG for more accurate BP estimation and proposes a method that does not require an initial cuff-based BP measurement, offering a promising approach for non-invasive, continuous BP monitoring.